Pengaruh Keragaman Produk Terhadap Keputusan Pembelian Pada Vierra Oleh-Oleh Kota Pekanbaru - Nurul Ilmi; Rosmayani Rosmayani (Pelantar Press, 2023)
The purpose of this study was to analyze, know and explain the effect of product diversity on purchasing decisions at Viera Souvenirs in Pekanbaru City. This research uses quantitative methods by processing the data obtained from the population and research sample of 100 respondents. The type and source of data used in this research is using secondary data and primary data where data collection is through distributing questionnaires and conducting interviews. Then from the data that has been collected the authors identify and classify the data using descriptive analysis methods, namely conducting research from data that has been found in the field. From the results of the study, it was obtained that the product diversity variable was in the strongly agree category, and the purchase decision variable was in the strongly agree category. Then from statistical calculations there are results where product diversity has a significant effect on purchasing decisions at Viera Souvenirs in Pek anbaru City.